Α-MSH ameliorates corneal surface dysfunction in scopolamine-induced dry eye rats and human corneal epithelial cells via enhancing EGFR expression. (September 2021) - Chu, Chenchen; Huang, Yue; Ru, Yusha; Lu, Xiaoxiao; Zeng, Xiaoyu; Liu, Ke; Gan, Lu; Zhang, Yan; Zhao, Shaozhen
Abstract: Dry eye (DE) is a chronic, multifactorial ocular surface disease associated with visual disturbance, tear film instability, hyperosmolarity, ocular surface inflammation and damage. Effective intervention is necessary to control this disease. In this study we topically applied α-melanocyte stimulating hormone (α-MSH) on the ocular surface of scopolamine-induced DE rats and found that it promoted tear secretion, reduced tear breakup time and fluorescein sodium staining and increased the number of conjunctival goblet cells. To investigate the mechanism, protein array was conducted, which showed that α-MSH exerted its effects via epithelial growth factor receptor (EGFR) in the JAK-STAT signaling pathway. Furthermore, in vitro experiments showed that α-MSH protected human corneal epithelial cells (hCECs) by maintaining their migration ability and viability and decreasing apoptosis. However, blockade of EGFR abolished these protective effects. Moreover, α-MSH decreased the level of autophagy in benzalkonium chloride (BAC)-stressed hCECs via EGFR. These results demonstrated that α-MSH ameliorated lesions and restored ocular surface functions by upregulating EGFR expression. Highlights: The α-melanocyte stimulating hormone exhibits superior therapeutic performance in rat dry eye model. The α-MSH maintains cell activity and suppresses autophagy in BAC stressed human corneal epithelial cells. Mechanistically, α-MSH activates both EGFR and JAK pathways in the dry eye corneas and conjunctivas. The α-MSH-containing eye drop will be hopefully translated into a novel intervention modality to the dry eye.